Google AI: Maksimalkan Perangkat Pembelajaran untuk Guru Geografi SMA Kota Ternate: indonesia - Safitri, Yuni Andriyani; Aryuni, Vrita Tri; Nasution, Lely Adriani; Sufia, Rohana; Pasongli, Hernita; Hariyadi, Eko (Jurnal Abdimas Madani dan Lestari (JAMALI), 2025)
Along with massive technological developments, the need for work support automatically becomes unavoidable. Artificial intelligence (AI) is here to answer this need, including in the world of education. In schools, teachers are faced with the problem of improving the quality of adaptive and inclusive learning. Of course, this quality improvement must be supported by learning devices and media that are interesting and appropriate to students' needs. However, making conventional learning tools will be very energy and time consuming, not to mention the limited resources available. Referring to this condition, this PKM activity was carried out with the aim of making learning tools more efficient through the use of AI. This is of course in line with the spirit of the vision of an independent curriculum, namely realizing education that is relevant and supported by technology. The target audience for this activity is high school geography teachers throughout Ternate City who are members of the Geography MGMP. This activity is held at SMAN 5 Ternate City. The use of a variety of AI-based Google service products will be introduced in this activity through a tutorial/practice method directly with the teacher. The stages in this PKM activity include preparation, implementation, evaluation, data analysis and reporting. The focus in this service activity is innovation and technology transfer to teachers in developing learning tools according to the demands of 21st century learning.